The Radioprotective Effects of Curcumin and Trehalose Against Genetic Damage Caused By I-131 - Jafarpour, Seyed Masoud (Indian J Nucl Med, 2018)
BACKGROUND: Thyroid cancer has been growing rapidly during the last decades. Radioiodine-131 (I-131) as an appropriate therapy modality is currently using in the treatment of cancer and hyperthyroidism diseases. This radiotracer is considered as a cause of oxidative DNA damage in nontarget cells and tissues. The aim of this study was to investigate the effects of curcumin and trehalose on the level of DNA double-strand breaks (DSBs) caused by I-131 in human lymphocytes. MATERIALS AND METHODS: First, 6-mL blood samples were taken from each of the five volunteers. After 1 h of preincubation with the antioxidants, a total of 20 μCi I-131/2 mL (blood + NaCl) was added to each sample, and then, the samples were reincubated for 1 h. Lymphocytes were separated and the mean DSB levels were measured for each sample through γ-H2AX assay to evaluate the effects of antioxidants. RESULTS: After 1-h incubation with I-131, the DSBs increased by 102.9% compared to the control group (0.343 vs. 0.169 DSB/cell; P = 0.00). Furthermore, compared to the control + I-131 group, curcumin and trehalose reduced the DSBs by 42% and 38%, respectively. There was a significant decrement (P = 0.00) in the levels of DSBs of the curcumin + I-131 and trehalose + I-131 subgroups compared to the control + I-131 subgroup. Furthermore, there was no significant relationship between the radioprotective effect of curcumin and trehalose (P = 0.95). CONCLUSION: The use of curcumin and trehalose as antioxidant can reduce the numbers of DSBs caused by I-131. Meanwhile, the radioprotective effect of curcumin was more than trehalose.